PENGARUH EKUITAS MEREK, PERSONAL SELLING, DAN HARGA PREMI TERHADAP KEPUASAN NASABAH ASURANSI TAKAFUL DANA PENDIDIKAN PADA ASURANSI TAKAFUL KELUARGA KANTOR REPRESENTATIF KEBUMEN - Rooswitasari, Tyas; Suryoko, Sri; Ngatno, Ngatno (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Public awareness of the importance of insurance countinues to rise, which is evident from the increasing number of people insured by 92,5% in 2013. It becomes a major opportunity for the insurance company, either the conventional insurance or Islamic insurance. In Indonesia, Islamic insurances have a good opportunity because the majority Moslem in Indonesia. But, the lack of differentiation is one the biggest reasons why Insurance lagged behind terms of penetration, distribution development, and product. Asuransi Takaful Keluarga is a pure Islamic insurance that was founded in 1994. This company is enganged in life insurance and some types of products are Asuransi Takaful Dana Pendidikan, Takaful Linksalam Alia, Takaful Linksalam Ahsan, Takaful Linksalam Istiqomah, and Takaful Linksalam Ahsan. While it has been long standing, a decline in customers from 2009 through 2013 for customers of Asuransi Takaful Dana Pendidikan in Representative Office Kebumen. The purpose of the research is to determine the effects of brand equity, personal selling, and price of premium to customers satisfaction of Asuransi Takaful Dana Pendidikan at Asuransi Takaful Keluarga Representatif Office Kebumen. The type of the research is explanatory research. The sample in this research were 97 respondents who are customers of Asuransi Takaful Dana Pendidikan. Data was collected by using interview technique, while the research instruments using a questionare. The results were analyzed using SPSS software assistance. The results of the research show that brand equity, personal selling, and price of premium have positive and significant effects on customers satisfaction amounted to 69,6%. Variable with the biggest effects to customers satisfaction is price of premium with the Beta value on multiple linear regression was 0,600. Advices can be given are strengthen brand equity though the promotion, improving personal selling through agents friendliness and patience in front of customers, and maintain a price of premy. Customers satisfaction can be improved by repair the service provided.